A Secure Self-Synchronized Stream Cipher. (26th May 2018) - Daneshgar, Amir; Mohebbipoor, Fahimeh
Abstract: We follow two main objectives in this article. On the one hand, we introduce a security model called LORBACPA + for self-synchronized stream ciphers which is stronger than the blockwise LOR-IND-CPA, where we show that standard constructions as delayed CBC or similar existing self-synchronized modes of operation are not secure in this stronger model. Then, on the other hand, following contributions of Millérioux et al., we introduce a new self-synchronized stream cipher and prove its security in LORBACPA + model.